Comunidades de Prática para Associações de doentes - Criação de plataforma de partilha de melhores práticas - Henriques, Inês Morgado (2022)
Project Work presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence